2010
DOI: 10.1016/j.jamcollsurg.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Verified Centers, Nonverified Centers, or Other Facilities: A National Analysis of Burn Patient Treatment Location

Abstract: Background-Although comprehensive burn care requires significant resources, patients may be treated at verified burn centers, non-verified burn centers, or other facilities due to a variety of factors. The purpose of this study was to evaluate the association between patient and injury characteristics and treatment location using a national database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 15 publications
(19 reference statements)
2
25
0
1
Order By: Relevance
“…The only recognized mechanism for assessing and confirming the quality of care provided in a burn center is verification by the American Burn Association (ABA)(11). However, in the US, non-verified (self-designated) burn centers outnumber verified burn centers(10), and half of all patients are treated outside of burn centers altogether(12). Additionally, outside of the US, there are only 4 ABA verified burn centers(13).…”
Section: Introductionmentioning
confidence: 99%
“…The only recognized mechanism for assessing and confirming the quality of care provided in a burn center is verification by the American Burn Association (ABA)(11). However, in the US, non-verified (self-designated) burn centers outnumber verified burn centers(10), and half of all patients are treated outside of burn centers altogether(12). Additionally, outside of the US, there are only 4 ABA verified burn centers(13).…”
Section: Introductionmentioning
confidence: 99%
“…15 Patients may prefer to remain near their families, homes, and primary care doctors. 15 Patients may prefer to remain near their families, homes, and primary care doctors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, verified patients trended toward having fewer comorbidities. 27 The next article addresses the question of appropriate referral to burn centers. This study reported that in North Carolina 48% of the burn patients who were admitted to nonburn centers met ABA criteria for transfer to verified burn centers.…”
Section: Epidemiologymentioning
confidence: 99%